Theory of mind in mild cognitive impairment subtypes: a systematic review - Guerrero Oyarzún, Eduardo (2024)
It is well known that social cognition functioning is impaired in Alzheimer's disease and other dementias, but its performance in different subtypes of mild cognitive impairment is less known. Objective: Systematic review aimed at collecting and summarizing studies that analyze the functioning and trajectory of the theory of mind in patients with amnestic, non-amnestic, single- and/or multidomain mild cognitive impairment. Materials and methods: The search, selection and extraction of studies followed PRISMA guidelines, and the quality assessment of selected studies was performed according to STROBE guidelines. Results: Fifteen out of 16 studies published between 2013 and 2023 that met the inclusion criteria showed that the theory of mind is impaired in all types of mild cognitive impairment, especially the amnestic type, regardless of etiology and the diagnostic criteria used. Conclusions: Mild cognitive impairment, especially in the amnestic subtype, is associated with significant theory of mind deficits. Further longitudinal studies must investigate the course of theory of mind deficits in the different subtypes of mild cognitive impairment, and explore their behavioral and neural correlates.